2014
DOI: 10.1149/2.0681412jes
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance Enhancement of Activated Carbon Modified in the Propylene Carbonate Electrolyte

Abstract: This work demonstrates a novel electrochemical procedure to enhance the specific capacitance (C S ) of activated carbon (AC) in organic electrolytes for the electrical double-layer capacitors (EDLCs). An irreversible oxidation process which provides pseudocapacitance occurs on AC when the electrode potentials are more positive than 0 V in the propylene carbonate (PC) electrolyte containing 1 M tetraethylammonium tetrafluoroborate (TEABF 4 ). This modification has been optimized by repeating 5 times of 100 char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…From a comparison of the EIS spectra before and after the floating test at 0.3 V, the results in the low-frequency region do not follow the same trace and the large impedance arc in the lowfrequency region becomes clear after the test. Both results display a slight change at the AC/electrolyte interface, probably due to the formation of a thin, modified layer after the polarization at 0.3 V for 3000 s [6]. Similarly, deviation from the corresponding original EIS spectra of the freshly prepared electrodes becomes more and more obvious with the positive shift in the electrode potential to 0.4 and 0.5 V (see Fig.…”
Section: Potential Window Determination By Combination Of Potential-fmentioning
confidence: 75%
See 2 more Smart Citations
“…From a comparison of the EIS spectra before and after the floating test at 0.3 V, the results in the low-frequency region do not follow the same trace and the large impedance arc in the lowfrequency region becomes clear after the test. Both results display a slight change at the AC/electrolyte interface, probably due to the formation of a thin, modified layer after the polarization at 0.3 V for 3000 s [6]. Similarly, deviation from the corresponding original EIS spectra of the freshly prepared electrodes becomes more and more obvious with the positive shift in the electrode potential to 0.4 and 0.5 V (see Fig.…”
Section: Potential Window Determination By Combination Of Potential-fmentioning
confidence: 75%
“…After the floating test at 0.2, 0.3, and 0.4 V for 3000 s, the fluorine content slightly increases from 2.83 to 5.08, 5.48, and 6.43 at.%, respectively. Thus, the surface modification of AC is gradually accumulated with TEABF 4 when the electrode potentials are positively shifted from 0.2 to 0.4 V. On the other hand, the fluorine content was sharply promoted to 29.17 at.% after the floating test at 0.5 V for 3000 s. Therefore, massive electrolyte species (including TEABF 4 and PC) react with the as-received AC surface at 0.5 V. Accordingly, in our previous work [6], the upper potential limit for the electrochemical modification of the AC surface should be more negative than/equal to 0.5 V in order to enlarge the working potential window of AC with acceptable capacitive responses in 1 M TEABF 4 /PC. Based on the above results and discussion, the decomposition products of the electrolyte on the electrode surface cannot be simply used to determine the upper limit of the working potential window; e.g., certain products accumulated on the AC surface at 0.2 V (vs. Ag/AgNO 3 ) do not indicate the unacceptable limits of the working potential window.…”
Section: Potential Window Determination By Combination Of Potential-fmentioning
confidence: 77%
See 1 more Smart Citation
“…Reduction in the density of oxygen-containing functional groups and hydrophilic groups can increase the stability of AC electrodes in nonaqueous electrolytes (Kim et al, 2014;Dong et al, 2018). More electronrich functional groups such as N introduced into the delocalized pi-system of the carbon network also increases electrical conductivity and capacitance (Hulicova-Jurcakova et al, 2009;Shen et al, 2014;Chi et al, 2016;Yang et al, 2017). Recently, Simon and Gogotsi pointed out in Nature Materials that efforts should be directed toward the modification of the porous carbon/ electrolyte interface by preparing passive layers or designing specific properties for more opportunities to enlarge the operation voltage range of EDLC device (Simon and Gogotsi., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Others works have found that functional groups containing heteroatoms such as O and N are very favourable to improve the capacitance, and these groups can be introduced using different doping methods, as chemical oxidations, plasma treatment, or electrochemical treatments. [18,19,20]. The main aim of oxidation of a carbon surface is obtaining a more hydrophilic surface structure with groups such as carboxyl groups [21,22].…”
Section: Introductionmentioning
confidence: 99%